2022
DOI: 10.1021/acschemneuro.2c00531
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into the Misfolding and Dimerization Dynamics of the Full-Length α-Synuclein from Atomistic Discrete Molecular Dynamics Simulations

Abstract: The misfolding and pathological aggregation of α-synuclein forming insoluble amyloid deposits is associated with Parkinson’s disease, the second most common neurodegenerative disease in the world population. Characterizing the self-assembly mechanism of α-synuclein is critical for discovering treatments against synucleinopathies. The intrinsically disordered property, high degrees of freedom, and macroscopic timescales of conformational conversion make its characterization extremely challenging in vitro and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 85 publications
4
56
1
Order By: Relevance
“…5,6 There are no solution structures available in the PDB for the cytosolic form of αS. 17 Here, we only used the micellebound PDB structure of αS as the starting conformation for each repeat. These initially helical fragments rapidly converted to coils in our simulations (Figures S1 and S2), suggesting that our results were independent of the initial structures.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 There are no solution structures available in the PDB for the cytosolic form of αS. 17 Here, we only used the micellebound PDB structure of αS as the starting conformation for each repeat. These initially helical fragments rapidly converted to coils in our simulations (Figures S1 and S2), suggesting that our results were independent of the initial structures.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…44,45 In addition, the accuracy of the Medusa force field with the EEF1 implicit solvation model in the aggregation of functional amyloid peptides of suckerin 46 and pathological amyloid polypeptides of hIAPP 26 has been benchmarked by the standard MD simulations with an explicit solvent model in our prior studies. With significantly enhanced sampling efficiency, the DMD algorithm has been widely used to study protein folding and amyloid aggregation, both by our group 17,25,26 and by others. 27,28,47 Analysis Methods.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 To investigate the inhibition mechanism of SEVI against Aβ fibrillization, we systematically studied the interactions between Aβ42 and SEVI by applying multiple long-timescale discrete molecular dynamics (DMD) simulations. 51,52 DMD is a rapid and predictive MD algorithm widely used to study protein folding and misfolding by both our group 53,54 and others. 55−57 Our results revealed that SEVI was intrinsically disordered with dynamic formation of helixes and had a significantly weaker self-aggregation tendency compared to Aβ42.…”
Section: ■ Introductionmentioning
confidence: 99%
“…MD simulations offer atomistic-level insights into individual amylogenic protein conformations and their aggregates. For instance, the full-length α-synuclein monomer and dimer were investigated by means of atomistic discrete MD simulations [ 44 ]. The modeling results predicted the formation of partial helices around the N-terminus (residues 8–32).…”
Section: Introductionmentioning
confidence: 99%